THE EFFECT OF GENDER DIFFERENCES AND SELF ESTEEM TOWARD KINDERGARTEN STUDENTSâ COMMUNICATIVE COMPETENCE - Rusmala Dewi, Ni Made (Jurnal Pendidikan Bahasa, 2012)
Abstract Key words: self esteem, gender differences, communicative competence This study was designed as an ex-post facto which aimed at seeing the effect of self esteem and gender differences toward kindergarten studentsâ communicative competence. The samples were students at the age between 3-5 which were taken from TK A of 7 kindergartens around Denpasar and Badung area. The data were collected by using questionnaire, document analysis and observation.. The data were analyzed by using Two-way ANOVA with 2x2 factorial design.Â  The result of the analysis showed that there was no significant difference between male and female kindergarten students in their communicative competence. It was also found that there was no interaction between self esteem and gender toward kindergarten studentsâ communicative competence. Since the result showed an absence of interaction between self esteem and gender, post-hoc multiple comparison with Tukey test was not carried out. This study concluded that there was no significant difference between male and female kindergarten students regarding their level of self esteem. There were several factors that possibly affect the finding of this study. The factors were the process of gender acquisition, early bilingualism, positive self esteem among children and teachersâ questioning.